El «Diccionari etimològic i complementari de la llengua catalana»: els objectius - Gulsoy, Joseph (Caplletra. Revista Internacional de Filologia, 2015)
Abstract: The author points out, whith examples, the rich and profound etymological studies offered by Joan Coromines in DECAT, and responds to some of the criticism of the mentioned studies.